Bündische Jugend : eine neue Geschichte : 1918-1933 - Ahrens, Rüdiger 1981- (Moderne Zeit, 2015)
This study of youth movements in Germany at the time of the Weimar Republic provides a historical overview of youth groups that is closely tied to the historical sources. The author discusses the organizational development and ideological alignment of the youth groups, along with the interactions they had with one another. He explains how youth groups originated as a result of WWI; what kind of mentality was produced by the youth-group education, with its strong emphasis on militarization and "courage;" and how youth groups reacted to the proposals and claims of the National Socialist movement. The results allow us to draw conclusions about the political situation of the time, and the ways in which it led to the erosion of the republic and the consolidation of Nazi rule. At the same time, this study shows the long-term effects that came about from youth groups